(untitled) (Modern education and development, 2025)
The article discusses the technologies that model the human brain, which are widely used in data analysis, data mining, and decision-making. In society, artificial neural networks are bringing revolutionary changes in the economy, healthcare, education, transportation, everyday life, and other areas. With the help of these technologies, production efficiency increases, medical diagnostics becomes more accurate, education is individualized, and automated transportation systems work efficiently. However, they also raise ethical, social, and economic issues. The article examines the positive and negative impacts of artificial neural networks on society and discusses the necessary measures for their future development..